Pregnancy and chronic kidney disease: potential problems with pregnancy and the use of renal replacement therapy (literature review) - В.В. Безрук; Д.Д. Іванов; І.Д. Шкробанець; Т.П. Андрійчук; І.С. Семань-Мінько; Т.Р. Андрійчук; С.В. Юрнюк (Počki, 2025)
The article presents an analysis of theoretical and practical results of research on the problem of pregnancy management in women with existing chronic kidney disease, assessment of potential problems and risk factors for the development of complications during pregnancy in the setting of nephrological pathology. The article focuses on the use of renal replacement therapy in pregnant women.